2016
DOI: 10.18632/oncotarget.12279
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between 2D and quasi-3D gamma evaluations for both intensity-modulated radiation therapy and volumetric modulated arc therapy

Abstract: The aim of this work was to investigate correlations between 2D and quasi-3D gamma passing rates. A total of 20 patients (10 prostate cases and 10 head and neck cases, H&N) were retrospectively selected. For each patient, both intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) plans were generated. For each plan, 2D gamma evaluation with radiochromic films and quasi-3D gamma evaluation with fluence measurements were performed with both 2%/2 mm and 3%/3 mm criteria. Gamma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Figure 5 shows the daily distributions of the maxRMS by DFV for 5 different pcsr QA plans and 12 real treatment plans which were grouped into the corresponding plan class. Similar MLC position error was revealed by different other previous works [10][11][12][13].…”
Section: Mlc Movement Analysissupporting
confidence: 86%
“…Figure 5 shows the daily distributions of the maxRMS by DFV for 5 different pcsr QA plans and 12 real treatment plans which were grouped into the corresponding plan class. Similar MLC position error was revealed by different other previous works [10][11][12][13].…”
Section: Mlc Movement Analysissupporting
confidence: 86%
“…Secondly, the degree of modulation in VMAT plans for prostate cancers can also be lower than that for other cancers due to the small treatment field size and less irregular shape of the target volume. Although there has been no concern about the cancer-or structure-specific acceptance criteria for gamma analysis, the degree of modulation may affect the quantity and magnitude of errors, and several studies have reported similar results to ours [14][15][16]. In the study by Vieillevigne et al [16], which performed pretreatment verification for VMAT plans using three different detectors in 15 cases of prostate cancer, the GFRs were less than 2% and less than 7% for the acceptance criteria of 3%/3 mm and 2%/2 mm in all detectors, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies recently showed irrelevance of the 2D gamma passing rates toward the changes in the clinically relevant dose-volumetric parameters between the treatment plan and actual delivery [ 22 , 25 ]. Information of the 2D gamma evaluation is not enough to detect errors affecting delivered doses which are three-dimensional inside a patient's body [ 26 ]. Moreover, since gamma evaluation is a comprehensive evaluation tool for a plan as a whole and not an evaluation tool for the delivered doses to each organ individually, the dose delivery accuracy to each structure including the target volumes and OARs, could not be verified individually with gamma evaluation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy of the various 3D gel dosimeters is not adequate to be used in the clinic yet, owing to the high uncertainty. Some dosimeters recently introduced in the clinic are capable of measuring quasi-3D dose distributions, such as COMPASS™ system (IBA Dosimetry GmbH, Schwarzenbruck, Germany), ArcCHECK™ (Sun Nuclear Corporation, Melbourne, FL, USA), and OCTAVIUS 4D™ system (PTW, Freiburg, Germany) [ 22 , 26 , 28 ]. Although these dosimetry systems can provide more information than the 2D dosimeters, they have their own limitations.…”
Section: Discussionmentioning
confidence: 99%